Thrips of Ornamentals in the Southeastern US - Joe Funderburk; Stan Diffie; Jyotsna Sharma; Amanda Hodges; Lance Osborne (EDIS)
ENY-845, a 10-page illustrated fact sheet by Joe Funderburk, Stan Diffie, Jyotsna Sharma, Amanda Hodges, and Lance Osborne, describes the common thrips associated with ornamental plants in the southeastern U.S., their biology, feeding behavior and damage, natural enemies, sampling and identification. Includes references and a key representing thrips species from three families. Published by the UF Department of Entomology and Nematology, December 2007.